2007
DOI: 10.1097/01.aog.0000277712.67230.22
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Exteriorized Compared With In Situ Uterine Repair at Cesarean Delivery Under Spinal Anesthesia

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 14 publications
0
18
2
Order By: Relevance
“…Also, it has been reported that the elevation of the uterus promotes venous drainage and reduces vascular congestion, further contributing to decreased blood loss [12]. However, most studies do not support the argument that no significant difference exists between these two techniques regarding blood loss and hematocrit levels [2,11,12]. In our study, we also found no significant differences between two groups when comparing blood loss and hematocrit levels.…”
Section: Discussioncontrasting
confidence: 71%
See 4 more Smart Citations
“…Also, it has been reported that the elevation of the uterus promotes venous drainage and reduces vascular congestion, further contributing to decreased blood loss [12]. However, most studies do not support the argument that no significant difference exists between these two techniques regarding blood loss and hematocrit levels [2,11,12]. In our study, we also found no significant differences between two groups when comparing blood loss and hematocrit levels.…”
Section: Discussioncontrasting
confidence: 71%
“…The decreased blood loss might also be related to better visualization of the uterus and more rapid uterine repair after uterine exteriorization from the abdomen [15]. Also, it has been reported that the elevation of the uterus promotes venous drainage and reduces vascular congestion, further contributing to decreased blood loss [12]. However, most studies do not support the argument that no significant difference exists between these two techniques regarding blood loss and hematocrit levels [2,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations